UTeach a quarter of century in review: Impacts, challenges, and new directions in STEM teacher preparation - McGuire, Patrick; Urquhart, Mary; Enderson, Mary; Hughes, Kimberly; Marder, Michael; Goldberg, Elizabeth (American Journal of STEM Education, 2025)
This article provides a summary of the first quarter century of the UTeach secondary STEM teacher preparation program (from 1997-2022). In addition to UTeach program expansion and impact statistics, we highlight current challenges faced by secondary STEM teacher preparation programs, including overall declines in university-based enrollments. To conclude, we discuss new directions of UTeach and offer recommendations for ways that university-based stakeholders can work together with K-12 district partners to make a positive impact on teacher preparation and STEM education for the next 25 years.